EKSISTENSI UPACARA ADAT PERANG KETUPAT DI DESA TEMPILANG SEBAGAI KEKAYAAN BUDAYA DI KABUPATEN BANGKA BARAT - Dea Amanda Putri; Akbar Al Masjid (Jurnal Ilmu Budaya, 2022)
The tradition of ketupat war held in Air Lintang Village, Tempilang District, West Bangka Regency as a research object aims to introduce and describe one of the cultural wealth in West Bangka Regency. Researchers also worked to find the meaning and values that became the background of the history of the war. This research uses qualitative descriptive research to get descriptive data in the form of oral, and written from a person or group and observe behavior. Data collection is carried out by observing the object to be studied, interviewing cultural figures, and documenting to strengthen the resulting data. This tradition of ketupat war ceremony began in 1883 and was carried out by the chieftain to fight the invaders/pirates. This happened at the same time as a lost girl was eaten by a crocodile demon. Then community leaders flocked to carry out the Village Taber Ritual to avoid disasters by collaborating so as to create a tradition in Tempilang Village, namely the Ketupat War. This ketupat war has the meaning of being able to avoid evil spirit spirits and subtle mahlauk who intend badly to disturb the local community and can clean up all ugly things in the future life. This tradition also contains values including cultural values, social values, local wisdom values, and educational values that can be used as lessons or guidelines in life and can shape the character of the nation's generations.